(untitled) (Research, Society and Development, 2024)
Zygomatic implants have become a highly effective alternative for oral rehabilitation in patients with severe maxillary atrophy, offering a durable and functional solution when other methods, such as bone grafts, are not feasible. However, the installation of zygomatic implants presents various technical and clinical challenges. Intraoperative complications during the procedure may compromise osseointegration and increase the risk of adverse outcomes. This article aims to review the primary complications associated with zygomatic implant installation, examining their causes, diagnosis, prevention, and management. Through a literature review, the paper explores the complexities of the procedure and emphasizes the importance of a meticulous approach to minimize risks and optimize outcomes.